A kinetic study on simultaneously boosting the mass and fixed-carbon yield of charcoal production via atmospheric carbonization. (August 2017) - Alonso, Maria Zabalo; Tran, Khanh-Quang; Wang, Liang; Skreiberg, Øyvind
Abstract: The mass and fixed-carbon yield of charcoal produced from woody biomass via atmospheric carbonization can be simultaneously improved by harnessing the phenomenon of secondary char formation as a result of prolonged contact time between pyrolysis gas and solid (char). In this study, the carbonization of forest residues in comparison with their stem wood was studied by means of a thermogravimetric analyzer operated non-isothermally at atmospheric pressure with a heating rate of 10K/min and a final temperature of 800ºC. Forest residue (tops and branches) and stem wood samples of Norway spruce, birch and oak trees collected from forests in Southern Norway were used as feedstock. The work focused on analyzing the effect of the process parameters (feedstock particle size, initial sample mass, and the residence time of volatiles released during the process) on the devolatilization kinetics of the carbonization process. The kinetic analysis was performed assuming the distributed activation energy model (DAEM) and three pseudo-components (hemicellulose, cellulose, and lignin).